Scalable Ambient Synthesis of Hydroxyl-Rich Cyclodextrin Potassium Metal-Organic Frameworks for High-Efficiency Iodine Capture - Cai, Yibin (Langmuir : the ACS journal of surfaces and colloids, 2025)
Developing high-performance reusable adsorbents is critical for radioactive iodine pollution control. Herein, we report the ambient-temperature scalable synthesis of hydroxyl-rich cyclodextrin potassium metal-organic frameworks (CD-K-MOF) via an ultrasound-assisted green protocol. CD-K-MOF was extensively characterized with various techniques, including TEM, FT-IR, Raman, and XPS, and batch experiments were conducted to evaluate the iodine adsorption performance. The adsorbent exhibits a micromesoporous hierarchy with a record-high surface area (1151 m2/g), achieving exceptional iodine capture capacities of 1.48 g·g-1 (vapor, 75 °C) and 638.4 mg·g-1 (cyclohexane solution). DFT calculations revealed that the porous frameworks, along with oxygen-enriched regions (notably hydroxyl groups), generate localized positive electrostatic potential (ESP), enabling strong electrostatic iodine adsorption. To enhance practical deployability, electrospun polyacrylonitrile fiber membranes incorporating CD-K-MOF were fabricated, exhibiting superior iodine adsorption capability and robust cycling stability. These findings provide mechanistic insights and highlight the potential of scalable MOFs as sustainable materials for environmental remediation and radioactive iodine mitigation